2022
DOI: 10.3390/plants11223054
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorous Supplementation Alleviates Drought-Induced Physio-Biochemical Damages in Calligonum mongolicum

Abstract: Calligonum mongolicum is a phreatophyte playing an important role in sand dune fixation, but little is known about its responses to drought and P fertilization. In the present study, we performed a pot experiment to investigate the effects of P fertilization under drought or well-watered conditions on multiple morpho-physio-biochemical attributes of C. mongolicum seedlings. Drought stress leads to a higher production of hydrogen peroxide (H2O2) and malondialdehyde (MDA), leading to impaired growth and metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
2
3
0
Order By: Relevance
“…Salinity-induced reduction in plant growth may be due to low uptake of mineral nutrients (Askari-Khorasgani et al, 2017), such as potassium (K + ), as a result of excess Na + accumulation (Chakraborty et al, 2016). In the present study, a similar phenomenon was observed, as increased saline stress (SS) led to impaired growth features (stem height, root length, leaf area, stemleaf-root fresh and dry weight; Figures 1A-H plasma membrane causing ionic imbalance, inhibiting metabolic processes, eventually declining plant growth (Mittler et al, 2011;Kaya et al, 2019;Ullah et al, 2022b;Ullah et al, 2022c). In the present study, gamma-aminobutyric acid (GABA) was applied under SS to investigate whether or not it can mitigate salinity-induced adverse effects on mungbean growth and metabolism.…”
Section: Exogenous Gaba Improved Growth Features Of Mungbean Plants U...supporting
confidence: 78%
See 1 more Smart Citation
“…Salinity-induced reduction in plant growth may be due to low uptake of mineral nutrients (Askari-Khorasgani et al, 2017), such as potassium (K + ), as a result of excess Na + accumulation (Chakraborty et al, 2016). In the present study, a similar phenomenon was observed, as increased saline stress (SS) led to impaired growth features (stem height, root length, leaf area, stemleaf-root fresh and dry weight; Figures 1A-H plasma membrane causing ionic imbalance, inhibiting metabolic processes, eventually declining plant growth (Mittler et al, 2011;Kaya et al, 2019;Ullah et al, 2022b;Ullah et al, 2022c). In the present study, gamma-aminobutyric acid (GABA) was applied under SS to investigate whether or not it can mitigate salinity-induced adverse effects on mungbean growth and metabolism.…”
Section: Exogenous Gaba Improved Growth Features Of Mungbean Plants U...supporting
confidence: 78%
“…The damages of salinity stress can be avoided by plants using several mechanisms, such as (i) the removal of toxic salt ions or their compartmentation within vacuoles or old tissues, (ii) the synthesis of compatible solutes, and (iii) the upregulation of non-enzymatic and enzymatic antioxidant defense mechanisms against salt-induced oxidative stress (Kaya et al, 2010a;Rahman et al, 2019;Mostofa et al, 2021). Salinity stress causes photoinhibition, which leads to an accumulation of untapped energy that destroys the photosynthetic apparatus, resulting in the formation of reactive oxygen species (ROS; Gururani et al, 2015;Polash et al, 2019;Ullah et al, 2022c). Increasing ROS levels weaken the antioxidant apparatus in cells, causing lipid peroxidation (MDA), which affects the membrane permeability and structure of the cell membrane, and causes damage to lipids, proteins, and nucleic acids (Tanveer, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, APX and GPX remained unchanged at 20-, 25-, 30-, and 40 °C but decreased at 35 °C. It has been suggested that germination increases mitochondrial respiration, which produces excess reactive oxygen species (ROS) that activate antioxidant defences [ 24 ] to protect themselves from ROS-induced oxidative damage [ 53 57 ], which corroborates our findings. CAT, POD, GPX, and APX are the major ROS-scavenging enzymes that reduce H 2 O 2 to reduce potential cellular damage associated with H 2 O 2 .…”
Section: Discussionsupporting
confidence: 90%
“…ephemerals, resurrection plants, and perennials with no active leaves in the dry season) they cannot effectively take up nutrients, and thus the addition of fertilizer would not impact plant biomass. By contrast, phreatophytes, that remain active despite water scarcity, can benefit from higher nutrient availability, improving their tolerance to drought (Ullah et al, 2022;Tariq et al, 2022b). For instance, phreatophytes such as A. sparsifolia and Calligonum mongolicum under N fertilization increased root and shoot biomass, antioxidant defence system, osmolytes and nutrients accumulation (Zhang et al, 2020(Zhang et al, , 2021b; Table S1).…”
Section: Fertilizationmentioning
confidence: 99%